Sustainable food networks, hybridization and values: a case study in Castilla y León (Spain) - Sánchez-Hernández, José Luis (Frontiers in Sustainable Food Systems, 2024)
Sustainable food networks involve different food supply arrangements which attempt to construct a more sustainable, democratic, and egalitarian food system. Since the concept appeared at the end of the 20th century (labelled as ‘alternative food networks’), two approaches have been employed to explore these initiatives. The ‘view of differences’ emphasizes alternativeness and opposition to the hegemonic food system, governed by large food production and retail firms. The ‘view of influences’ highlights the complex interactions between the mainstream food system and these more sustainable initiatives. As a result of these interactions, many sustainable food networks apply organizational practices similar to those of mainstream companies: this process has been called ‘hybridization’. The present article studies the process of hybridization in the sustainable food networks based in the Spanish provinces of Salamanca and Zamora (region of Castilla y León). An inventory of sustainable food initiatives across the region has been compiled and semi-structured interviews have been conducted with initiatives all along the food value chain. According to qualitative data recorded in the interviews, it is argued that the broad set of hybrid practices embodied in these sustainable food networks are legitimized by the members’ values because they contribute to achieving three key objectives: protecting the environment, promoting health, and fostering local development. These three goals frame an ‘inward’ notion of sustainability rooted on the product itself that is likely to turn these networks less transformative, but also more resilient against the competition of the mainstream companies.